(untitled) (Makerere University Journal of Agricultural & Environmental Sciences, 2019)
Land application of bio-solids is the cheapest and most convenient method of disposal of bio-solids worldwide, but it is unclear if the bio-solids in Uganda are safe for land application. The objective of this study was to establish the impact of ageing on quality and safety of bio-solids from Bugolobi Wastewater Treatment Plant (BWTP) in Uganda’s capital city, Kampala, for land application. Nine out of 14 beds in each of the four blocks (Block 1: fresh bio-solids; Block 2: settling bio-solids; Block 3: maturing biosolids and Block 4: mature bio-solids) were randomly sampled for quality and for biosafety. For quality, bio-solids were analysed for electrical conductivity (EC), N, P and K concentrations, and their respective stocks; organic matter (OM) content and biosolid organic carbon (BOC) stocks. For bio-safety, bio-solids were screened for Escherichia coli and Salmonella. Data were subjected to ANOVA after checking for normality and equal variance assumptions, using GenStat statistical package 14th edition. Ageing of bio-solids had a significant impact on EC; OM and E. coli. The EC was highest in the mature bio-solids (4556±173) µS cm-1 and smallest in fresh biosolids (3494±124) µS cm-1. These EC values exceed the maximum permissible limits. Similarly, microbial counts were highest for E. coli in the mature sludge (3946±86) ‘000’ CFU g-1 and smallest in the fresh bio-solids (633±22.9) ‘000’ CFU g-1. Out of the 36 bio-solid samples, one tested positive for salmonella. The bio-solids are not safe for use as agricultural input, nor for general release into the environment.